Synthesis and Characteristics of Valeric Acid-Zinc Layered Hydroxide Intercalation Material for Insect Pheromone Controlled Release Formulation. (25th October 2016) - Ahmad, Rozita; Hussein, Mohd Zobir; Sarijo, Siti Halimah; Wan Abdul Kadir, Wan Rasidah; Yun Hin, Taufiq-Yap
Abstract : A new intercalation compound of insect pheromone, valeric acid (VA), based on zinc layered hydroxide (ZLH) as host release material, was successfully prepared through coprecipitation method. The as-produced organic-inorganic nanolayered material, valerate nanohybrid, VAN, shows the formation of a new peak at lower 2 θ angle with basal spacing of 19.8 Å with no ZnO reflections, which indicate that the intercalation of anion between the inorganic ZLH interlamellae was accomplished. The elemental, FTIR, and ATR analyses of the nanohybrid supported the fact that the intercalation with the percentage anion loading was calculated to be 23.0% (w/w). The thermal stability property of the resulting nanohybrid was enhanced compared to the unbound anion. Field emission scanning electron micrograph of the ZnO has a nonuniform granular structure but transforms into flake-like structure with various sizes after the intercalation process. Release kinetics of anion from the interlayer of intercalated compound exhibited a slow release behavior governed by the pseudo-second-order kinetic model at different pHs of aqueous media. The valerate anion was released from VAN with the highest release rate at pH 4. These findings provide the basis to further development of controlled release formulation for insect pheromone based on ZLH intercalation.